Renal Cell Carcinoma with Inferior Vena Cava Thrombus: A Case Report - Anisuzzaman, Md; Hosain, Nazmul; Rashid, Zulfiqar (Cardiovascular Journal, 2022)
The incidence of venous extension to the inferior vena cava (IVC) of renal cell carcinoma (RCC) is markedly increased recently mostly due to the advances in diagnostic modalities. Such vascular invasion implies a heightened biologic behavior and a surgical challenge during the course of treatment. Here we discussed a case with study of the classification guidelines, recent diagnostic tools and up-to-date therapeutic modalities for RCC with IVC tumor thrombi. Also added to the discussion are the prognostic significance regarding the pathologic nature of vascular invasion, cephalad extent of thrombi and any associated distant metastasis. Cardiovasc j 2022; 15(1): 111-115